Immunoprevention and immunomodulation of yellow fever: A scoping review of global and Latin American evidence - Clímaco de Jesús Pérez Molina; Flor Elena Chavarro Bermeo; Arlin Martha Bibiana Pérez Hernández (PLoS ONE, 2026)
Background Yellow fever (YF) remains a major global public health challenge, with recurrent outbreaks in Africa and the Americas despite the long-standing availability of a highly effective vaccine. In recent years, outbreaks in Brazil and Colombia (2024–2025) have underscored persistent barriers to achieving optimal vaccination coverage and have highlighted the predominantly reactive nature of many public health responses to YF transmission. Objective To map and synthesize evidence published between 2020 and 2025 on YF immunoprevention and immunomodulation at global, Latin American, and Colombian levels, identifying advances, gaps, and implications for public health policy. Methods A scoping review was conducted following PRISMA-ScR guidelines. Eligible sources included original research, reviews, and official documents addressing vaccination strategies, safety, and immune responses. Publications in English, Spanish, and Portuguese from January 2020 to September 2025 were retrieved from major databases and grey literature sources. Data were tabulated and descriptively synthesized. Results Seventy-eight documents met inclusion criteria. The literature consistently supported the high efficacy of a single 17D vaccine dose, with fractional dosing validated as an emergency strategy in contexts of vaccine shortage. Immunological evidence confirmed strong and durable humoral and cellular responses, consistent with foundational studies conducted prior to 2020. However, important gaps persist, particularly regarding immunogenicity and safety in Latin American populations, older adults, pregnant women, and people living with HIV. In Colombia, universal vaccination campaigns during the 2025 outbreak improved coverage but revealed weaknesses in pharmacovigilance, local research capacity, and sustained prevention strategies. Conclusions The 17D vaccine remains the cornerstone of YF control. However, sustaining elimination goals requires not only maintaining ≥95% vaccination coverage but also strengthening pharmacovigilance systems, generating locally relevant immunological evidence, and transitioning from reactive outbreak responses to more proactive, context-sensitive vaccination strategies.